Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning di Kelas V Sekolah Dasar - Nadiyah, Ulza; Suardiman, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The objective of this research is to describe an integrated thematic learning process improvement to the model of discovery learning in fifth grade elementary school 09 Bandar Buat Padang City. The approach used in this research is qualitative and quantitative. The research aspects of the teacher first cyclethe average value of 79,7% with enough qualification, in the second cycle to 90,6% with excellent qualifications. Aspects of the students' first cycle the average value of 79,7% with enough qualification,in the second cycle to 90,6%, with excellent qualifications. The student learning outcomes first cycle with an average value of 69 with the predicate B-,increased in the second cycle to 87,5 with the predicate A. Thus the model of discovery learning can enhance the learning process and student learning outcomes.